Artificial intelligence in financial and investment decision-making - Carl Heinz Daube (ZBW – Leibniz Information Centre for Economics, 2024)
The aim of this working paper is to provide a brief introduction to artificial intelligence and highlight specific potential applications in financial and investment decision-making. On the one hand, it is about where AI is already being used today in many areas of the financial industry. On the other hand, the aim is to show examples of what will be possible in the near future and where AI might lead to better, more sound decisions – – Ziel dieses Working Papers ist es, eine kurze Einführung in die Künstliche Intelligenz zu geben und konkrete Einsatzmöglichkeiten in der Finanz- und Investitionsentscheidung aufzuzeigen. Dabei geht es zum einen darum, wo KI heute schon in vielen Bereichen der Finanzindustrie zum Einsatz kommt. Zum anderen geht es darum exemplarisch aufzuzeigen, was in naher Zukunft möglich sein wird und wo es auf der Basis von KI zu besseren, fundierteren Entscheidungen kommen könnte.
Keywords: G00; 330; AI; Artificial Intelligence; investment decision; finance decision